E Pengembangan Perangkat Pembelajaran Berbasis STEAM Dalam Penanaman Nilai Karakter Pancasila Anak Usia Dini - Nur Ika Sari Rakhmawati; Sri Setyowati; Muhammad Reza (Jurnal Ilmiah POTENSIA, 2023)
Social, scientific, and technological changes require a flexible curriculum. The prototype curriculum emphasizes essential material, project-based learning, and teacher flexibility. Early childhood education must develop Pancasila character value, a new learning outcome for the students. This study uses the ADDIE development model consisting of 5 stages: analysis, design, develop, implement, evaluate. The setting of this study was in two Early childhood institutions in Surabaya and Sidoarjo. The Evaluation stage involves formative and summative evaluation at each development stage. This lesson plan and learning resources based STEAM for developing Pancasila character value was 85.4% based on an expert questionnaire. Therefore, it can be concluded that STEAM-based teaching modules to implant Pancasila values are ideal learning reference materials for kindergarten teachers